UNIVERSITY STUDENTS’ PERCEPTIONS OF USING CHATGPT - Prima, Stefanus; Hartono, Dang Arif (English Education Study Program STKIP PGRI Pacitan, 2024)
Since its launch in late 2022, the use of ChatGPT has garnered controversies despite its benefits and potential in helping foreign language study. While many scholars have warned against its risk to academic integrity, there are only a few studies investigating the perception of Indonesian higher education students in using ChatGPT. This article examines the perceptions of Indonesian higher education students in using ChatGPT by utilizing open-ended questions distributed via Google Form. Data from 16 participants currently enrolled in a hospitality study program were gathered. All participants reported that they mostly use ChatGPT to assist them with university assignments. For language study, nine students reported that they found it useful, especially to learn new vocabulary and its straightforward explanation compared to the teacher’s explanation. More studies are needed to explore how English learners can gain benefits by using ChatGPT and how teachers can utilize ChatGPT to explore more alternatives in promoting learner’s autonomy and more enhanced learning experience.